A summary of TCRP Report 88 A guidebook for developing a transit performance-measurement system. - Ryus, Paul (Research results digest (Transit Cooperative Research Program), 2003)
"This summary was prepared by Paul Ryus, principal investigator, Kittelson & Associates, Inc."